1999
DOI: 10.1097/00007435-199905000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity, Substance Use, and HIV/STD Knowledge Among Detained Male Adolescents With Multiple Versus First Admissions

Abstract: Youth with multiple versus first admissions are at higher risk of HIV/STD infections through their lifetime and recent sexual activities. Interventions targeted to this population will need to address the barriers to and facilitators of condom use, strategies to promote positive attitudes toward condoms, and strategies to reduce the high level of alcohol and substance use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Motivational enhancement in the current study was not directly focused on altering sexual risk behaviors, per se, so our effect for overall sexual risk was surprising. Heightened levels of sexual risk behavior occur in combination with substance use and intoxication among adolescent detainees (Devieux et al, 2002;Gary et al, 2000;Harwell et al, 1999;Kingree et al, 2002). Future efforts to directly address reducing participation in high-risk sexual behaviors among incarcerated adolescents are definitely warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motivational enhancement in the current study was not directly focused on altering sexual risk behaviors, per se, so our effect for overall sexual risk was surprising. Heightened levels of sexual risk behavior occur in combination with substance use and intoxication among adolescent detainees (Devieux et al, 2002;Gary et al, 2000;Harwell et al, 1999;Kingree et al, 2002). Future efforts to directly address reducing participation in high-risk sexual behaviors among incarcerated adolescents are definitely warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Out of approximately 2.4 million juvenile arrests each year, more than 203,000 are for offenses related to substance use (Snyder, 2002). As is true for many sexually active populations, heightened levels of sexual risk behavior occur in combination with substance use and intoxication among adolescent detainees (Devieux et al, 2002;Gary et al, 2000;Harwell, Trino, Rudy, Yorkman, & Gollub, 1999;Kingree, Braithwaite, & Woodring, 2002). One study (Castrucci & Martin, 2002) found a strong association between regular substance use and sexual risk (including multiple sex partners, inconsistent condom use, and trading sex for money or drugs) among their sample of incarcerated adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This survey also found that females who reported sexual abuse had their first sexual encounter at an earlier mean age than those who reported no sexual abuse, and abused respondents were significantly more likely to not use any form of contraception than detainees without a history of sexual abuse. A 1997 survey of 486 male youth at a Philadelphia juvenile facility reported substantially higher than background rates of ever having sexual intercourse, having intercourse within the last six months, an age at first sex of Յ 13 years, and having at least eight sexual partners in their lifetime [40].…”
Section: Sexual Health Pregnancy and Stdsmentioning
confidence: 98%
“…[1][2][3][4][5][6] Other studies have revealed high levels of risky sexual behaviors and sexually transmitted diseases among juvenile detainees. 7,8 Interventions and treatments to reduce mental health problems and at-risk behaviors of juvenile delinquents are also available and have been fairly well-described. [9][10][11][12] Studies have examined a wide range of health behaviors and problems among juvenile delinquents, but few have examined weight-related issues in this vulnerable population.…”
Section: Introductionmentioning
confidence: 99%